DYNAMICS OF IL12 CYTOKINE EXPRESSION IN HUMAN MACROPHAGES AFTER TREATMENT WITH DIOXIN - D. Y. Oshchepkov; E. V. Kashina; E. V. Antontseva; E. A. Oshchepkova; V. A. Mordvinov; D. P. Furman (Вавиловский журнал генетики и селекции)
Interleukin IL-12 is a key proinflammatory cytokine, synthesized by macrophages, but the information concerning the dioxin effect on its expression is still fragmentary. The presence of previously identified potential dioxin responsive elements (DREs) in the regulatory regions of IL12A and IL12B genes, encoding IL-12 subunits IL-12p35 and IL-12p40, respectively, suggests direct activation of these genes by binding of the dioxin/AhR/ARNT complex to DREs. This work proves the binding capacity of these DREs by gel shift assay. The study of the dynamics of IL12A and IL12B gene expression in the human macrophage cell line U937 revealed no influence of dioxin on IL12A expression. In contrast, activation of IL12B gene expression with subsequent inhibition was noted. The observed dynamics can be explained by direct activation of the expression by the dioxin-containing complex and subsequent inhibition of the expression because of oxidative stress caused by dioxin. Thus, the well-known dioxin influence on the immune system can be associated with the difference in the dioxin effect on the expression dynamics of the genes encoding IL-12 subunits.